Teaching and learning in further education : diversity and change - Huddleston, Prue; Unwin, Lorna (London, United Kingdom : Routledge, 1997)
This book has been written, primarily, for people who are embarking on a teaching career in colleges of further education (FE) and for those already teaching who may wish to review their approaches to and understanding of the process of teaching and learning.
1. Where will I teach? -- 2. The student body: Who will I teach? -- 3. Diverse curricula: What will I teach? -- 4. Approaches to learning -- 5. Teaching strategies -- 6. Assessment and recording achievement -- 7. Evaluation, reflection and research -- 8. Professional development -- 9. Networks and support agencies.
Includes bibliographical references and index.
Keywords: TEACHING